2009
DOI: 10.1021/la9001175
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Phase Reduction of Cuprous Oxide (Cu2O) Nanoparticles Accompanied by a Morphology Change during Ethanol-Assisted Spray Pyrolysis

Abstract: Metallic copper nanoparticles are produced by spray pyrolysis of copper nitrates with an addition of ethanol as cosolvent at 600 degrees C. Depending on the synthesis temperature, two interesting reaction pathways are found: below 525 degrees C, approximately 10% of hollow Cu(2)O parent particles are oxidized to CuO and then reduced to Cu, but at higher temperature, the remaining Cu(2)O takes a direct path to Cu, accompanied by a morphology change. These interesting reaction regimes are discussed in the aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 28 publications
1
31
0
1
Order By: Relevance
“…CuO decomposes at >450 °C to Cu 2 O [43] and finally decomposes to metallic copper at higher temperatures. It is also reported that Cu 2 O reduces directly to Cu at >525 °C [44].…”
Section: Adsorbent Preparationmentioning
confidence: 92%
“…CuO decomposes at >450 °C to Cu 2 O [43] and finally decomposes to metallic copper at higher temperatures. It is also reported that Cu 2 O reduces directly to Cu at >525 °C [44].…”
Section: Adsorbent Preparationmentioning
confidence: 92%
“…However, with the further increase of the Cu/TiO 2 ratios above 6% wt, the Cu + /Cu 2+ ratios slightly decreased. The reduction of Cu 2+ into Cu + , which resulted from the incorporation of Cu ions into the TiO 2 lattice as well as from the oxalic acid cleaning and UV irradiation processes (rolled as reducing agents) led to oxygen vacancies in the TiO 2 and CuO lattice [39,40]. The formation of oxygen vacancies led to a certain degree of limitation in the Cu 2+ reduction [41].…”
Section: Resultsmentioning
confidence: 99%
“…Assynthesized catalysts nanoparticles were collected by a glass membrane filter with 1 µm pores (Milipore). More details about experimental setup are available elsewhere (Lee et al, 2007;Firmansyah et al, 2009Firmansyah et al, , 2012.…”
Section: Preparation Of Catalystsmentioning
confidence: 99%
“…, where R g is the gas constant, F is the Faraday constant, ν + and ν -are respectively the valences of the cation and anion, and λ 0 is the limiting ionic conductance (Reid et al, 1987;Firmansyah et al, 2009Firmansyah et al, , 2012 (Reid et al, 1987;Firmansyah et al, 2009Firmansyah et al, , 2012 , η B is the solvent viscosity in cP, V A is the molar volume of solute A at its normal boiling temperature in cm 3 mol -1 , and ϕ is the association factor. As a result, the diffusion coefficient of Pt(acac) 2 in ethanol is estimated to be 4.1 × 10 -6 cm 2 s -1 and the diffusion coefficient of TEOS in water is estimated at 8.0 × 10 -6 cm 2 s -1 .…”
Section: Test For Catalytic Activity Of No Reductionmentioning
confidence: 99%
See 1 more Smart Citation